Bone turnover in amenorrhoeic and eumenorrhoeic women distance runners - Zanker, C. L.; Swaine, I. L. (Scandinavian Journal of Medicine & Science in Sports, 1998)
Bone remodelling has not been assessed in women distance runners with chronic amenorrhoea. The purpose of this study was to compare indices of bone turnover and energy balance in runners with chronic amenorrhoea, runners with a history of regular menstrual cycles and sedentary controls. Subjects comprised 3 groups of 9 women, matched for age [mean+/-SEM: 27.2+/-1.8 yrs] and categorised as amenorrhoeic runners (AmR), eumenorrhoeic runners (EuR) and eumenorrhoeic sedentary controls (SC). Serum concentrations of bone formation markers [osteocalcin (OC), carboxy-terminal propeptide of type 1 collagen (P1CP), bone alkaline phosphatase (BAP)], E2, total T3 and IGF-1 were measured from a fasting morning blood sample. Urine levels of bone resorption markers [pyridinoline (Pyr) and deoxypyridinoline (Dpyr)] were measured and corrected for creatinine excretion. Mean daily energy balance (EB) was calculated by subtracting dietary energy intake (EI) from energy expenditure (EE) estimated from reported activity patterns over 7 days. The results showed that all bone turnover markers were lower in AmR than in EuR or SC (P<0.001: OC, BAP and P1CP; P<0.05: Pyr and Dpyr). Furthermore, when z-scores for each bone marker in runners were calculated against mean values for SC (by subtracting each measure of bone turnover from the mean value for SC and expressing the difference as a fraction of the SD of this mean value), bone resorption appeared to outweigh formation in AmR, but not in EuR. Serum concentrations of E2, T3 and IGF-1 were also lower in AmR than in EuR or SC (P<0.001: all hormones), as was EB (P<0.001). These findings suggested that in AmR there was some factor which was reducing bone turnover and in particular, bone formation. This factor might have been linked to an energy deficit and the effects of this deficit on body mass, body composition and metabolism. Scand J Med Sci Sports 1998 Feb;8(1):20-6